COMPREHENSIVE PARTNERSHIP OF THE UNITED STATES OF AMERICA AND INDONESIA TRADE AND INVESTMENT AS A WAY TO STRENGTHEN BILATERAL RELATIONS WITH INDONESIA UNDER OBAMA ADMINISTRATION - Meylan Novan Kurnianto (HI 16 UMY 188, 2016)
*188 The United States-Indonesia relationship is important to the national interest of both countries, and it would only grow more in the years to come. The relation between the United States and Indonesia has run in right path lately. Recognizing the need to elevate the United States-Indonesia relationship to whole new level, President Barack Obama together with former President Soesilo Bambang Yudhoyono institutionalized a new era in the U.S-Indonesia cooperation by announcing bilateral comprehensive partnership. This undergraduate thesis aims to analyze on how the implementation of comprehensive partnership, so it could strengthening bilateral relation between the United States and Indonesia by using one concept and two theories. The data collected in this thesis are secondary data obtained from books, book sections, journal article, news item, website, and document from website. This undergraduate thesis shows that there is a need for the U.S and Indonesia to elevate their relations to higher level. Both countries the United States and Indonesia have recognized that a 21st century friendship between nations cannot be based on one aspect only, but it also needs to contain another aspect. Trade and Investment becomes the safest way to strengthen bilateral relation between the United States and Indonesia because it will provides abundant advantage for both countries directly